Kemampuan Penguasaan Konsep pada Materi Peristiwa Banjir melalui Problem Based Learning dengan Bantuan Zoom Meeting (Penelitian Kualitatif Deskriptif Pada Siswa Kelas V Sd Negeri Cipeujeuh Kulon 3 Kecamatan Lemahabang Kabupaten Cirebon) - Maryani, Deassy; Aeni, Ani Nur; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2021)
This study aims to measure students' conceptual mastery ability through Problem Based-Learning on flood event materials assisted by zoom meetings. The type of study used is qualitative with descriptive method. Subjects in this study were fifth-grade students at SDN Cipeujeuh Kulon 3 for the 2020/2021 academic year. The results showed that 1) the lesson plan preparation showed a very good category. 2) The activities of teachers during the implementation of PBL showed a very good category. also accompanied by student activities that give a positive response Furthermore, 3) half 38.46% students in the very good category, almost half 46.15% students in the good category, and a small part of 15.38% students in the moderate category.Â  Based on the results, it concluded that the concept mastery ability of the fifth-grade students received a positive response. after the implementation ofÂ  PBL supported by good planning, teacher performance, and student activities.